Does Alignment Technique in Medially Stabilized Total Knee Arthroplasty Affect the Patellofemoral Joint Biomechanics and Patient-reported Outcomes at 1 Year? A Prospective Registry-based Cohort Study - Samuel W. King, BM BCh, MRCSEd; Nicolas Silvestrini, PhD; Anne Lübbeke, MD, DSc; Hemant Pandit, DPhil, FRCS (Tr & Orth); Hermes H. Miozzari, MD, PD (Arthroplasty Today, 2025)
Background: Current femoral components may produce a nonanatomical trochlea position with kinematic alignment (KA). This study compared effects of alignment on patellar tilt and patient-reported outcomes in medially stabilized total knee arthroplasty (MS-TKA). Methods: MS-TKA patients from a prospective registry-based consecutive cohort were subdivided by alignment technique and patella resurfacing status. Impact of alignment technique stratified by patellar resurfacing on 1-year patellar tilt was investigated with analysis of variance. For alignment technique impact stratified by patellar resurfacing on 1-year Western Ontario and McMaster Universities Arthritis Index (WOMAC), analysis of covariance including preoperative WOMAC pain and function scores as covariates were performed. Spearman's rank correlation was computed for patellar tilt vs WOMAC pain and function at 1 year. Results: 295 MS-TKAs were included: mechanical alignment in 168 (56.9%), patella resurfaced in 137 (46.4%), mean age 68.0 years, mean body mass index 30.6 kg/m2. More women had nonresurfaced patellae (74.3%; P = .011), otherwise baseline demographics, radiological parameters, WOMAC, and lateral release rates were similar between groups. At 1 year, patellar tilt was higher for KA vs mechanical alignment (7.31 vs 5.90; P = .028) in both resurfaced and nonresurfaced TKA. No effect of alignment on baseline-adjusted WOMAC at 1 year was found in both resurfaced and nonresurfaced TKA. One-year patellar tilt did not correlate with WOMAC pain (rs = −0.004; P = .954) or function (rs = 0.016; P = .832). Conclusions: Despite greater patellar tilt at 1year with KA, this study suggests alignment technique in MS-TKA does not adversely impact patella-femoral joint in a clinically significant manner, leading to similar patient-reported outcomes regardless of patellar resurfacing status.